"It's just a bit like a rollercoaster": a longitudinal qualitative study exploring a model of the phases of voice hearing. Issue 4 (2nd October 2019) - Bogen-Johnston, Leanne; deVisser, Richard; Strauss, Clara; Hayward, Mark
ABSTRACT: Background : Existing models of the phases of hearing distressing voices have relied upon data from cross-sectional designs and the retrospective accounts of hearers. There is a need for a longitudinal study to examine the phases of voice hearing over time. Methods : A longitudinal, mixed-methods design was used. Stage 1 - semi-structured interviews were conducted at nine monthly intervals at four time-points with voice hearers (n = 12) from Early Intervention in Psychosis Services. Data were Thematically Analysed. Stage 2 – findings were mapped onto an integrated model of voice hearing. Results : Stage 1 analysis generated higher-order themes: "Common Pathway", "Voices Stop", "Voices Continue but Beliefs Change", and "Voices Continue but Beliefs do not Change". Stage 2 analysis generated a potential framework for a revised model of voice hearing over time with three novel sub-group pathways. Conclusions : Findings suggested three novel sub-group pathways. Beliefs about voices influenced the course of voice hearing. Changes in beliefs were associated with acceptance, meaning-making and recovery: whereas beliefs that did not change were associated with ongoing voice-related distress. Findings highlight the importance of therapeutic conversations in supporting hearers to explore their experiences with voices.